The pagan stone [compact disc, unabridged] - Roberts, Nora (Roberts, Nora. Sign of seven trilogy, 2008)
At ten years of age, Gage Turner and his friends unleash an ancient, powerful force when they spill blood over a pagan stone. Years later, Gabe returns to his hometown to help his childhood friends halt the death-dealing demonic forces that ravage the town every seven years.